Managing students’ motivation: an empirical study from self-determination perspective - Hassan, Arif (2014)
Purpose/Objective: There always has been serious concern on students’ academic performance in schools and institutions of higher learning. Mostly it is addressed in terms of lack of motivation. However, little attention has been given to the reasons of poor motivation. The Self-Determination Theory (SDT) of motivation provides a new perspective of motivation. The paper examines the students’ motivation and study engagement using SDT framework. It examines the role of teachers in creating autonomy supportive learning climate that contribute to students’ intrinsic motivation and study engagement.